Period Homes - Styles & Original Features An Easy Reference Guide. - Yorke, Trevor (Britain's Architectural History., 2021)
This book aims to help the reader recognise the common British architectural styles and original features from each period, whether they just want to find out more about a particular property, or are trying to restore one.